TRANSFORMATION OF ISLAMIC PHILANTHROPY BY THE IDRISIYYAH TARIQA IN THE DIGITAL ERA - Munandar, Siswoyo Aris; Fahrurrozi, Fahrurrozi (Balai Penelitian dan Pengembangan Agama Makassar, 2024)
Abstract This article explores the transformational role of the Tarekat Idrisiyyah in the practice of Islamic philanthropy in the digital era through the Agen Care initiative. By utilizing information and communication technology, Agen Care has succeeded in increasing the efficiency of donation management, expanding the reach of social programs to remote areas, and increasing public awareness of the importance of social piety. Programs such as waqf, direct cash assistance, house renovation, education and health implemented by Care Agents have had a significant positive impact on the community. However, several technical and sustainability challenges are still faced. Implementation of these new strategies opens up opportunities to strengthen the role of the Idrisiyyah Tarekat as a relevant and effective agent of social change in the digital era. This article highlights how technology can strengthen and expand charitable activities, fulfill religious obligations, and contribute to creating a more prosperous and socially just society.